Keterlibatan Masyarakat Desa Landungsari Dalam Kebijakan Pendaftaran Tanah Sistematis Lengkap (RechtJiva, 2024)
The government has accelerated the program by encouraging public participation. Landungsari Village in Malang district was selected as the locationof the PTSL year 2023. Public involvement in PTSL activities in Landungsari Village is demonstrated by the participation citizens who are actively registering their land. Although there is already public participation in the PTSL, in fact certain stages still do not involve public involvement This research is a type of sosio legal research that uses sociological jurisprudence. Secondary data obtained indirectly from law and official document. The population in this research is all officer in ATR/BPN District Malang and and all the citizens in Landungsari. The sample in this research uses purposive sampling method and that are analyzed using analytical descriptive method. Based on the results of the research, it is known that the regulation substance is uncomplete norm about public participation, and then the structure is complete because have Puldatan, and then the culture not complete because citizen not understand of the law. Solution this research a need socialization and maximum communication to enthusiasm to follow PTSL.